Rozwiązania metodologiczne w badaniach nad seksualnością dziecka = Methodological solutions in the research on the sexuality of a child - Ratkowska-Pasikowska, Justyna; Pasikowski, Sławomir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article includes a review of solutions applied in the methodology of research on the sexuality of a child. It has been accomplished based on a list of the mainstream foreign and Polish research on the sexuality of a child as well as the analysis of the content of the EBSCO service. As a result some changes that occurred over a period of time have been observed. They concerned the range of the number of research tied with the issue of the sexuality of a child over a period of time, the preferences of data gathering methods, schemes of research as well as technologically advanced solutions. Possible factors deciding on the result of the executed review have also been discussed.
Keywords: seksualność; dziecko; badania; metodologia